Lyophilized NLC of Cinacalcet HCl: Physics of Tablet Compression and Biopharmaceutical Characterization - Nayak, Sabita; Sruti, Jammula; Patra, Chinam Niranjan; Jena, Goutam Kumar (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Cinacalcet Hydrochloride (CINH) is a BCS class IV drug. It is mainly used for the treatment of chronic renal disease and parathyroid cancer. It exhibits poor oral bioavailability less than 25%. The main objective is to improve the bioavailability and stability of CINH by formulating the lyophilized Nanostructure Lipid Carrier (NLC) into tablet dosage form. Materials and Methods: In this research, Glycerylmonostearate (GMS), labrasol, tween 20 were the main excipients selected for the formulation of NLC. Hot high speed homogenization and ultra-sonication method was used for the NLC formulation of CINH. The selected NLC formulation was lyophilized using three different cryoprotectants at three different concentrations. Physics of tablet compressions study was conducted for the selected lyophilized powders. The pharmacokinetic study was conducted to determine the improvement in bioavailability of the CINH. The cytotoxicity study was performed by using MTT assay method to know the cell viability. Results: The lyophilized NLC formulation exhibited high drug entrapment efficiency content with particle size less than 200nm. Physics of tablet compression study showed lyophilized NLC containing 15%w/v mannitol exhibited plastic deformation. Pharmacokinetic study showed 5 folds increase in oral bioavailability for Lyophilized NLC (LNLC3) in comparison to aqueous suspension of CINH. Minimum viability was determined as 94% which indicates the safety of the incubated formulations. Conclusion: Lyophilized NLC formulation has the potential to improve the oral bioavailability with high drug loading, stability, and cell viability for CINH with desirable tableting parameters for making tablet.
Keywords: Compactibility; Cryoprotectant; Crystalinity; Bioavailability and Cytotoxicity